Flow of the Ross ice Shelf, Antarctica, is modulated by the ocean tide - Brunt, KM; Matt King; Fricker, HA; Macayeal, DR (2010)
The ice streams feeding the Ross Ice Shelf, Antarctica, have large tidally modulated (sinusoidal and stick-slip) flow, but the interaction with the ice shelf is poorly understood. We show that the flow of the Ross Ice Shelf front, up to âˆ¼650 km from the ice streams, exhibits smooth, sinusoidal motions corresponding to tidal modulation. These observations suggest a possible linking of the ice shelf with the ice streams to form a unified system that responds to small perturbations in stresses associated with ocean tides. If this is the case, the presence of the sinusoidal motion but the absence of stickÌˆCslip motion suggests there is damping of very high-frequency signals. The dissimilar signatures of the motions observed in the ice streams and at the front of the ice shelf present challenges to model development aimed at understanding the dynamics of coupled ice-stream/ice-shelf flow and the movement of ice across grounding lines.